Overestimation of molecular and modelling methods and underestimation of traditional taxonomy leads to real problems in assessing and handling of the world’s biodiversity - Löbl, Ivan (Zootaxa, 2014)
Since the 1992 Rio Convention on Biological Diversity, the earth’s biodiversity is a matter of constant public interest, but the community of scientists who describe and delimit species in mega-diverse animal groups, i.e. the bulk of global biodiversity, faces ever-increasing impediments. The problems are rooted in poor understanding of specificity of taxonomy, and overestimation of quantitative approaches and modern technology. A high proportion of the animal species still remains to be discovered and studied, so a more balanced approach to the situation is needed.